2022
DOI: 10.1111/1751-7915.14082
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of microalgae and their microbiomes

Abstract: Microalgae comprise a phylogenetically very diverse group of photosynthetic unicellular pro-and eukaryotic organisms growing in marine and other aquatic environments. While they are well explored for the generation of biofuels, their potential as a source of antimicrobial and prebiotic substances have recently received increasing interest. Within this framework, microalgae may offer solutions to the societal challenge we face, concerning the lack of antibiotics treating the growing level of antimicrobial resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…In our previously published datasets we detected a surprisingly high diversity of quorum quenching agents that are known to be involved in disturbing/interrupting the synchronization of bacteria within a community 21 , 28 , 30 , 32 . In total, almost 638 enzyme candidates were predicted, most of them hydrolases (number of hits: 321).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previously published datasets we detected a surprisingly high diversity of quorum quenching agents that are known to be involved in disturbing/interrupting the synchronization of bacteria within a community 21 , 28 , 30 , 32 . In total, almost 638 enzyme candidates were predicted, most of them hydrolases (number of hits: 321).…”
Section: Resultsmentioning
confidence: 99%
“…However, biofilm formation can be attacked at various key positions, for example by biotechnological approaches targeting the capability of adherence, the production of extracellular polymeric substances, or by disturbing the bacterial communication. Although, the diversity of known enzymes and microbes affecting biofilms and potential pathogenic microorganisms is still rather limited, a promising source for finding novel bioactive compounds against biofilm-forming fish pathogenic bacteria is the fascinating world of microalgae and their associated bacterial communities 20 , 21 . Previous research showed that microalgae are surrounded by a natural community of beneficial bacteria, including interesting strategies that make this microbiota able to out-compete undesirable opportunistic bacteria such as fish pathogens or even human pathogens 21 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…or Roseobacter sp., respectively, against Vibrio anguillarum [57,58]. However, certain algae may have the opposite effect by sequestering vital nutrients and limiting their availability to bacteria [59]. Moreover, various algal cultures have been found to contain extracellular polymeric substances (EPS) that possess inhibitory properties against multiple bacterial and fungal isolates.…”
Section: Algae and Their Effects On Gut Microbiome Profilementioning
confidence: 99%
“…Microalgae biomass and their bioactive compounds, such as polyunsaturated fatty acids (PUFAs), pigments, amino acids, peptides, scytonemins, pterins and phenolic compounds, have been shown to demonstrate a wide range of therapeutic effects [ 18 ]. Importantly, some of the microalgae and bioactive compounds exhibit antioxidant, anti-inflammatory, and immune-modulatory properties, and improve insulin sensitivity that could potentially alleviate diabetes mellitus [ 18 , 19 , 20 , 21 ]. Table 1 summarizes the bioactive compounds present in various sources that have been particularly identified in certain microalgae species and their activity on diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%